2013
DOI: 10.1089/cyber.2013.0025
|View full text |Cite
|
Sign up to set email alerts
|

The Facebook Influence Model: A Concept Mapping Approach

Abstract: Facebook is a popular social media Web site that has been hypothesized to exert potential influence over users' attitudes, intentions, or behaviors. The purpose of this study was to develop a conceptual framework to explain influential aspects of Facebook. This mixed methods study applied concept mapping methodology, a validated five-step method to visually represent complex topics. The five steps comprise preparation, brainstorming, sort and rank, analysis, and interpretation. College student participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 42 publications
2
73
0
1
Order By: Relevance
“…One young adult participant described that "uploading photos contributes to setting the social norm. I don't think we upload photos to set social norms, we upload photos to share and connect with other people and a byproduct of that is setting social norms" (Moreno, Kota, Schoohs, & Whitehill, 2013). While more information is clearly needed to understand the influence of social media on health risk behaviors, these early studies provide support for further research.…”
Section: Influence Of Displayed Alcohol On Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…One young adult participant described that "uploading photos contributes to setting the social norm. I don't think we upload photos to set social norms, we upload photos to share and connect with other people and a byproduct of that is setting social norms" (Moreno, Kota, Schoohs, & Whitehill, 2013). While more information is clearly needed to understand the influence of social media on health risk behaviors, these early studies provide support for further research.…”
Section: Influence Of Displayed Alcohol On Social Mediamentioning
confidence: 99%
“…The Facebook Influence Model describes the influence of "identity development" on Facebook, and interventions could build upon this source of influence (Moreno, Kota, et al, 2013). Researchers could consider linking Facebook advertisements to a user's displayed alcohol content.…”
Section: Facebookmentioning
confidence: 99%
“…According to a 2013 Japanese white paper [25], the number of Internet users in Japan expanded by 8.3 times in the 13 years after 1997, social media use has become widespread, and especially among young people, communication behaviour has diversified. A previous study [45] also revealed the behavioural influence of social media, particularly Facebook. The influence of Facebook is that the platform provides quick connection: people can reach anyone, bonding across cultures and distances through the network, presenting the best side of themselves, and showing off their accomplishments to everyone they friended on Facebook.…”
Section: Generation-specific Factorsmentioning
confidence: 76%
“…Sites de redes sociais, por exemplo, permitem aos jovens manterem contato com seus amigos mesmo quando eles não são capazes de se reunir em situações não mediadas (Boyd, 2008). Além disso, eles são meios pelos quais o adolescente é capaz de se relacionar com outros grupos sociais e buscar pessoas com as quais ele mais se identifique (Barker, 2009;Moreno et al, 2013). Isso é importante porque, durante a adolescência, o pertencimento a um grupo não apenas oferece apoio, mas também tem um significado especial na construção da identidade.…”
Section: Motivações E Atividades Dos Adolescentes Com Mídias Sociaisunclassified